Physician outreach during a pandemic: shared or collective responsibility? - Lanphier, Elizabeth (Journal of medical ethics, 2022)
In ‘Ethics of sharing medical knowledge with the community: is the physician responsible for medical outreach during a pandemic?’ Strous and Karni note that the revised physician’s pledge in the World Medical Association Declaration of Geneva obligates individual physicians to share medical knowledge, which they interpret to mean a requirement to share knowledge publicly and through outreach. In the context of the COVID-19 pandemic, Strous and Karni defend a form of medical paternalism insofar as the individual physician must reach out to communities who may not want, or know to seek out, medical advice, for reasons of public health and health equity. Strous and Karni offer a novel defence of why physicians ought to intervene even in insular communities, and they offer suggestions for how this could be done in culturally sensitive ways. Yet their view rests on an unfounded interpretation of the Geneva Declaration language. More problematically, their paper confuses shared and collective responsibility, misattributing the scope of individual physician obligations in potentially harmful ways. In response, this reply delineates between shared and collective responsibility, and suggests that to defend the obligation of medical outreach Strous and Karni propose, it is better conceptualised as a collective responsibility of the medical profession, rather than a shared responsibility of individual physicians. This interpretation rejects paternalism on the part of individual providers in favour of a more sensitive and collaborative practice of knowledge sharing between physicians and communities, and in the service of collective responsibility.